2003
DOI: 10.14411/eje.2003.054
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations of Coccinella magnifica, a myrmecophilous coccinellid to aggression by wood ants (Formica rufa group). II. Larval behaviour, and ladybird oviposition location1

Abstract: Abstract. Like adults, larvae of the myrmecophilous ladybird Coccinella magnifica are rarely attacked by Formica rufa ants on for aging trails, but more often attacked on ant-tended aphid colonies. Larvae of the non-myrmecophile Coccinella septempunctata, to which C. magnifica was compared, were more readily attacked by ants in both situations. To avoid or counter ant aggression when foraging for aphids, C. magnifica larvae exhibit three main tactics: they may feed on un-or non-tended aphids; when feeding on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 23 publications
1
45
0
1
Order By: Relevance
“…Published work supports the view that C. magnifica adults and larvae are less vigorously attacked by F. rufa than are other ladybirds, notably C. septempunctata (Donisthorpe, 1919(Donisthorpe, -1920Majerus, 1989;Sloggett et al, 1998). The adults also use physical defence on colonies of F. rufa-tended aphids, where the probability of ant attack is much greater .…”
Section: Coccinella Magnlflca Ant -Associationssupporting
confidence: 62%
See 1 more Smart Citation
“…Published work supports the view that C. magnifica adults and larvae are less vigorously attacked by F. rufa than are other ladybirds, notably C. septempunctata (Donisthorpe, 1919(Donisthorpe, -1920Majerus, 1989;Sloggett et al, 1998). The adults also use physical defence on colonies of F. rufa-tended aphids, where the probability of ant attack is much greater .…”
Section: Coccinella Magnlflca Ant -Associationssupporting
confidence: 62%
“…Coc cinella magnifica's chemical counter to ant-aggression probably involves chemical repellence rather than chemical mimicry (Sloggett, 1998;Sloggett, unpub. data), and C. magnifica defence behaviour is, like its probable chemical adaptation, effective against most ant species (Arnold and others in Majerus, 1994, p.151;Sloggett et al, 1998). Coccinella magni fica may thus be potentially able to coexist with a wide variety of ant species, both typical and accidental associates, without suffering high ant aggression.…”
Section: Coccinella Magnifica Associations With Non-formica Antsmentioning
confidence: 98%
“…In myrmecophilous species, the larvae tend to move slowly and inconspicuously, as has been observed for Coccinella magnifica (Redtenbacher), P. luteorubra, and B. quadripunctata [33,40,42]. The comparison between the myrmecophilous species C. magnifica and its close nonmyrmecophilous relative C. septempunctata (Linnaeus) has shown that C. magnifica uses physical, behavioral, and chemical defenses adapted from the general defenses observed in Coccinellidae [42,43].…”
Section: Behavioural Traitsmentioning
confidence: 83%
“…It is well known that ladybirds eat aphids. Coccinella septempunctata, a good model of a potential predator, is readily attacked by Formica rufa (Sloggett et al, 1998). All the ants studied, except F. cunicularia and F. fusca, protect aphid colonies from this predator to some extent.…”
Section: Discussionmentioning
confidence: 99%